To the history of hydrothermotherapy: pages of history - Samosiuk, I.; Orzheshkovsky, V.; Zukow, W.; Sikorska, A. (Journal of Education, Health and Sport, 2011)
In 1921 in London, was created by the International Society of Medical Hydrology, which included scientific societies of scientists from over 40 countries, in 1928 they were joined by scientists of the Soviet Union. In 1937 was organized by the International Federation of the health resort, which in 1947, renamed the "International Federation of Hydrotherapy and Climatology (FITEC). In 1999, Congress in Yalta, it was called "The World Federation of Hydrotherapy and Climatotherapy (FEMTEC). FEMTEC is the most representative association of Spa and health organizations in the world. FEMTEC composed of national Spa and health resorts associations and federations, as well as central state organizations dealing with Spa problems from many countries and continents. FEMTEC functions under the aegis of the World Health Organization and submits every three years report on its activities. The principal functions of the Federation are following: representing world thermalism matters and promote them internationally before states and public organization; international business-like co-operation in health resorts’ sector; study, research and experience exchanges in the sphere of Spa treatments; popularization of Spa and health resorts of the FEMTEC member-countries in different countries of the world. With a view of organizing fruitful activities of FEMTEC there function 4 permanent commissions: medical, economic, technical and social. FEMTEC members actively participate in international scientific symposia, exhibitions, conferences; there are held annual General Assembly, Executive Board and Executive Committee meetings. Every year FEMTEC organizes Scientific Congress along with a competition of scientific works, marks of the best thermalists etc. The Federation maintains close contacts with European Spas Association (ESPA), World Tourism Organization (WTO) and other international organizations. The Board of FEMTEC includes the following member: Prof. Nikolay Storozhenko - (Russia) President of FEMTEC from 1998, President National Spa Association D.M., Honored Physician (http://www.naturmed.unimi.it/femtec.html). In 1996 he joined the Federation of Russia, which was timed to the International Congress "The resort medicine, science and practice", held in May 1996 in St. Petersburg. In 1998 the Federation adopted the Ukrainian Association of Physiotherapists and health resort. One of the main problems is FEMTEC: cooperation of scientific institutions, exchange of information in the study of technological and scientific problems associated with water-and climate-through scientific committees, convening the annual congresses, conferences, symposia, seminars, publications, etc.